No deleterious circumference effects for T90 codends in an Australian fish trawl targeting tiger flathead, Platycephalus richardsoni - Broadhurst, Matt K.; Millar, Russell B. (Frontiers in Marine Science, 2024)
In an attempt to improve the selectivity of Australian fish trawls targeting tiger flathead, Platycephalus richardsoni (≥28 cm total length), the utility of four-seam codends with shortened lastridge ropes and comprising 71-mm meshes turned 90 o (T90) hung at the narrowest and widest coherent circumferences were compared against a traditional 91-mm diamond-mesh (T0) codend. 20Significant effects of codend configuration were limited to an increase in the catches of another commercially important species, latchet, Pterygotrigla polyommata by both T90 codends, and greater escape of some small tiger flathead from the wide 71-mm T90 codend than from the 91-mm T0 codend. Notwithstanding a need to investigate slightly larger T90 mesh sizes for the fishery, the data imply that unlike for most codend configurations, circumference does not negatively affect selection 25 in the stated designs, and might not require future regulation.